Surgery at a glance - Grace, P. A. [ (Pierce A.)]; Borley, Neil R. (At a glance series, 2009)
Following the familiar, easy-to-use at a Glance format, and now in full-colour, Surgery at a Glance is an accessible introduction and revision text for medical students. Fully revised and updated, this at a Glance provides a user-friendly overview of surgery to encapsulate all that the student needs to know.